FILM ANIMASI NABI YUNUS SEBAGAI MEDIA DAKWAH DI TPQ AL-GHAZALI DESA GUNUNG BUNDER 1 - AZIZA, ARBELLA; DZAKIYYAH, HASNA; ISNAWATI; FAIZ, MARCELINO; BERLIAN, PUTRI; HIDAYAT, RAHMAT; EL RAIHAN, ZULHAM (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
This study aims to find out whether the film can be used as a medium of da'wah, The subjects of this study are children who are in TPQ Al-Ghazali, The method used in this study is a descriptive method The results of the study showed that the animated film of the prophet Yunus can be used as a medium of da'wah, because children more easily understand the histories in the film of the prophet Yunus